O desempenho econômico do ativo intangível e do capital social realizado - uma análise empírica das empresas da BM&BOVESPA entre 2010 e 2012 - Moura Filho, Antonio Anésio de Aguiar (2015)
This research has developed a study about the influence that the intangible asset and the paid-up share capital exert on the economic development of business corporations through profit and debt. The business corporations BM&BOVESPA, having open capital, were the chosen corporate type, being thus possible to obtain data through their financial statements. Taking into account the period that ranges from 2010 to 2012, a total of 1.495 observations could be obtained. By estimating the regression model with panel data, the variables “Intangible Asset” and the “ Paid-up share capital” related to the profitability (rentability) and to the debt ( own resources and from a third-party) were analyzed . The results obtained from the estimation utilizing the chosen variables indicate that the intangible assets, in some cases, exert attraction on investments increasing coming from their own resources and also from a third-party; as well as on boosting profits. The paid-up share capital also suggested similar results.